Effect of ideal protein versus low‐fat diet for weight loss: A randomized controlled trial - Camilo A. Fernandez; Kaitlin Potts; Lydia A. Bazzano (Wiley, 2022)
Abstract Background Current guidelines call for peer‐reviewed evidence of efficacy and safety for commercial weight loss programs to be recommended as options for those seeking to lose weight. Objectives This study investigated the Ideal Protein (IP) system, a commercial weight loss program, compared to a guideline‐based, low‐calorie/low‐fat (LCLF) dietary behavioral intervention on body weight and CVD risk factors in adults with obesity. Methods In this randomized, assessor‐blinded, parallel‐group trial, 192 participants with body mass index (BMI) ≥30 and ≤49 kg/m2 were assigned to either the IP Phase I diet or LFLC diet interventions. The IP Phase I is focused on lean protein and vegetables with avoidance of fruit and dairy, while the LFLC diet goals include <30% of daily energy from fat, <7% from saturated fat, 55% from carbohydrate, and an energy deficit of 500 kcal/day. The primary endpoint was change in body weight at 3 months. Secondary endpoints included change in waist circumference (WC), hip circumference (HC), total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C) and high‐density lipoprotein cholesterol (HDL‐C), triglycerides (TG), fasting glucose (FG), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Results The mean ± SD of change in weight at 3 months was −9.6 ± 12.7 kg in the IP group as compared to −1.6 ± 27.2 kg in the LFLC group. The mean between‐group difference in change at 3 months was −8.1 kg (95% confidence interval [CI] −16.6 to 0.6; p = 0.05). Additional significant between‐group differences included WC, HC, TC, and TG levels, all favoring the IP group. There were no serious adverse events during the intervention period. Conclusions The present findings demonstrate the efficacy and safety of the IP weight loss program as compared to a guideline‐based LCLF dietary behavioral intervention among black and white adults with obesity and CVD risk factors, providing support for the effectiveness of the program.